Learning Styles of National University of Lesotho Nursing Students: Foundation in Improving Teaching-Learning Process - Shelile, Z. M.; Ntsóh, M. M. E. (Indian Journal of Nursing Sciences, 2024)
Background: Learning style preference impacts on how well groups of students respond to their curricula. The nursing educator’s goal is to creatively develop education techniques that are companionable with the preferred learning styles of students. Purpose: The purpose of this study was to determine the learning styles of the National University of Lesotho (NUL) nursing students and the findings will form a basis in improving the teaching-learning process. Methods: This study followed a quantitative cross-sectional design. The study took place at the National University of Lesotho which envisages being a vibrant African University, nurturing thought leaders. The English version of the VARK questionnaire was administered to 149 undergraduate nursing students in second, third, fourth, and fifth levels of study to determine their learning style preferences. Descriptive statistics were used to identify the learning styles of students. Results: There were more nursing students who preferred a unimodal learning styles (80.6%) than those who preferred a multimodal learning styles (19.4%). The bimodal learning style was the preferred style among multimodal learners in total sample and in each study level separately. Within the unimodal learners, 34.9%, 25.1%, 21.2%, and 18.8% of the nursing students were Kinaesthetic (K), Reading/Writing (R), Aural (A), and Visual (V) learners, respectively. Conclusions: The present study concluded that students have varied learning styles. The kinaesthetic is the predominant learning style among NUL nursing students. This preference jointly with the read/write preference suggests that teaching strategies that include hands-on experience and activities will be the most successful.